Productive And Energy Consumption Improvement With The Use Of A Linear Induction Motor In Cereal Drying Mechanics - Tanimoto, Sussumu C.; Bispo, Décio; Camacho, J.R. (Eletrônica de Potência, 2009)
The proposed work presents a research on the efficiency of a LIM - Linear Induction Motor [2][4][5][6][7], applied in a cereal drier discharge system, in order to substitute the conventional pneumatic piston system (conventional system). The work is based in the conventional system fault reduction concept, with a search for a robust and simple system, which also presents improved efficiency, low energy consumption showing technological innovation to the agricultural industry. A suitable simulator was assembled for the dryer discharge system and LIM. Operational tests were made, with the measurement of force and energy consumption. Finite Element Methods were used for comparative simulation and prototype force determination. The obtained results are very close to expected and are perfectly in agreement with the proposed final task.